Exploring the molecular mechanisms of Ag(I) transporters involved in bacterial Ag(I) resistance - Lithgo, Ryan (2022)
Silver (Ag(I)) displays multiple antimicrobial properties that have led to its widespread use in the medical field. However, extensive use of Ag(I) has led to the emergence of bacterial resistance to Ag(I). Resistance to Ag(I) was inferred through the presence of plasmid pMG101 that contains a gene cluster, sil, which allowed bacteria to survive six times the normal lethal dose of Ag(I). The proteins of the sil system were given putative functions based on their sequence homology to the more extensively studied cue and cus systems, involved in copper homeostasis. To date only SilE has been characterised. This work herein describes the functional and structural characterisation of three more of the proteins of the sil system; SilP, SilF and SilC.